Multi-modal single cell sequencing of B cells in primary Sjögren’s Syndrome (processed VDJ data). - Arvidsson, Gustav; Czarnewski, Paulo; Johansson, Alina; Raine, Amanda; Imgenberg-Kreuz, Juliana; Nordlund, Jessica; Nordmark, Gunnel; Syvänen, Ann-Christine (Uppsala University, 2024)
Meta data record for processed VDJ data from the publication "Multi-modal single cell sequencing of B cells in primary Sjögren’s Syndrome".
Abstract:

Primary Sjögren’s syndrome (pSS) is an autoimmune disease characterized by lymphocytic infiltration in the salivary and lacrimal glands, B cell activation, SSA/SSB autoantibodies and an increased risk of B cell lymphoma. By generating sorted B cell single-cell gene expression and BCR libraries from 24 pSS patients stratified by SSA/SSB antibodies and four healthy controls, we defined 16 B cell subtypes. Interferon response genes were upregulated in pSS across all B cell subtypes, with the highest levels in pSS with both SSAB antibodies. The SSAB group showed a higher proportion of naïve B cells and lower proportion of memory B cells compared with controls. Memory B cells from SSAB patients were not class switched and expressed unmutated VDJ sequences. IGHV1-69 repertoire frequencies were higher in pSS patients than controls and 1287 clonotypes were unique for pSS. The present study describes molecular differences which may enable stratification of pSS patients at improved resolution.

Repository content:

10X Genomics 5' VDJ (v1.1) BCR data from B cells from  Primary Sjögren's Syndrome (pSS) patients and healthy controls.

Output from cellranger (5.0.1) for all samples where targeted VDJ libraries were successfully created and sequenced (23/24 samples). Files to be used as input to, for instance,  the immcantation workflow or the Bioconductor R package scRepertoire. Data is available upon reasonable request.

Processed data files included for each sample:

*_filtered_contig_annotations.csv

*_filtered_contig.fasta

Command used to generate the files:

cellranger vdj \

--id="${sample}B" \

--sample=${bcrsamples} \

--fastqs=${fqdir} \

--reference="$CELLRANGER_VDJ_DATA/refdata-cellranger-vdj-GRCh38-alts-ensembl-5.0.0" \

--localcores=16 \

--localmem=112

List of files:

C001_B_filtered_contig.fasta 3.1M

C001_B_filtered_contig_annotations.csv 1.0M

C002_B_filtered_contig.fasta 9.8M

C002_B_filtered_contig_annotations.csv 3.2M

C003_B_filtered_contig.fasta 9.8M

C003_B_filtered_contig_annotations.csv 3.2M

C004_B_filtered_contig.fasta 12M

C004_B_filtered_contig_annotations.csv 3.8M

P001_B_filtered_contig.fasta 7.4M

P001_B_filtered_contig_annotations.csv 2.5M

P002_B_filtered_contig.fasta 9.1M

P002_B_filtered_contig_annotations.csv 3.1M

P003_B_filtered_contig.fasta 3.7M

P003_B_filtered_contig_annotations.csv 1.2M

P004_B_filtered_contig.fasta 11M

P004_B_filtered_contig_annotations.csv 3.6M

P005_B_filtered_contig.fasta 10M

P005_B_filtered_contig_annotations.csv 3.4M

P006_B_filtered_contig.fasta 13M

P006_B_filtered_contig_annotations.csv 4.4M

P007a_B_filtered_contig.fasta 4.9M

P007a_B_filtered_contig_annotations.csv 1.6M

P007b_B_filtered_contig.fasta 8.0M

P007b_B_filtered_contig_annotations.csv 2.7M

P008a_B_filtered_contig.fasta 8.8M

P008a_B_filtered_contig_annotations.csv 2.8M

P008b_B_filtered_contig.fasta 12M

P008b_B_filtered_contig_annotations.csv 3.8M

P009_B_filtered_contig.fasta 7.5M

P009_B_filtered_contig_annotations.csv 2.5M

P010_B_filtered_contig.fasta 15M

P010_B_filtered_contig_annotations.csv 5.0M

P011_B_filtered_contig.fasta 9.7M

P011_B_filtered_contig_annotations.csv 3.3M

P012_B_filtered_contig.fasta 12M

P012_B_filtered_contig_annotations.csv 4.1M

P013_B_filtered_contig.fasta 9.1M

P013_B_filtered_contig_annotations.csv 3.0M

P014_B_filtered_contig.fasta 11M

P014_B_filtered_contig_annotations.csv 3.8M

P015_B_filtered_contig.fasta 11M

P015_B_filtered_contig_annotations.csv 3.7M

P016_B_filtered_contig.fasta 13M

P016_B_filtered_contig_annotations.csv 4.2M

P017_B_filtered_contig.fasta 7.2M

P017_B_filtered_contig_annotations.csv 2.4M

P018_B_filtered_contig.fasta 15M

P018_B_filtered_contig_annotations.csv 4.9M

P019_B_filtered_contig.fasta 20M

P019_B_filtered_contig_annotations.csv 6.5M

P020_B_filtered_contig.fasta 10M

P020_B_filtered_contig_annotations.csv 3.5M

P021_B_filtered_contig.fasta 7.8M

P021_B_filtered_contig_annotations.csv 2.6M

P022_B_filtered_contig.fasta 9.4M

P022_B_filtered_contig_annotations.csv 3.1M

P023_B_filtered_contig.fasta 7.2M

P023_B_filtered_contig_annotations.csv 2.4M

_CHECKSUMS.txt 3.8K

_README.txt 637B
Keywords: Autoimmunity; Medical and Health Sciences; Medicin och hälsovetenskap; Autoimmunity and Inflammation; Autoimmunitet och inflammation